Effect of Warming on Growth, Grazing, and Community Composition of Free-Living Bacterioplankton in Subtropical Coastal Waters During Winter and Summer - Gu, Bowei; Lee, Candy; Ma, Xiao; Tan, Yehui; Liu, Hongbin; Xia, Xiaomin (Frontiers in Microbiology, 2020)
Global warming is considered a major threat to marine ecosystems, which effects on bacterioplankton activity, diversity, and community composition. However, few studies focused on the potential effects of warming on bacterioplankton in the subtropical coastal waters in different seasons. Here we investigated the influences of warming on growth, grazing and community composition of bacterioplankton in Hong Kong coastal waters during winter and summer via 1-day incubation experiments. Our results revealed that without grazers, bacterioplankton displayed higher growth rate during summer compared to winter, while warming only significantly increased the growth rate of bacterioplankton in winter. Grazers with size < 5 μm were major predators of bacterioplankton. Warming had little effect on grazing in summer but significantly enhanced grazing rates of > 5 μm grazers in winter. In both seasons, warming had little influence on bacterial diversity and community composition. Nevertheless, in family and OTU level, bacterioplankton had different responses to grazing and warming which may result from the selective grazing preference of predators and different temperature optima for bacterioplankton. Furthermore, the presence of > 5 μm and < 5 μm grazers would result in significant increase of some bacterial families to warming. Together, our results suggest that warming have direct impacts on bacterioplankton in subtropical coastal waters during winter and may thus affect global biogeochemical cycles.